2016
DOI: 10.18632/oncotarget.13745
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum uric acid and glaucoma severity in primary angle closure glaucoma: a retrospective case-control study

Abstract: Uric acid (UA) is a major antioxidant molecule and has been hypothesized to have a protective effect on the central nervous system against oxidative damage. We prospectively investigated the serum concentration of UA in primary angle closure glaucoma (PACG), and explored the association between serum concentration of UA and the severity of PACG. Using a retrospective case-control study design, 886 PACG subjects and 994 control subjects who attended the Eye & ENT Hospital of Fudan University, were eligible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…Our previous study on UA levels in patients with primary angle closure glaucoma demonstrated that UA levels were reduced compared to those observed in normal controls, and that the level of UA was only negatively associated with the disease severity of primary angle closure glaucoma (Li et al. ). However, previous data regarding the serum levels of UA in patients with POAG are not available.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Our previous study on UA levels in patients with primary angle closure glaucoma demonstrated that UA levels were reduced compared to those observed in normal controls, and that the level of UA was only negatively associated with the disease severity of primary angle closure glaucoma (Li et al. ). However, previous data regarding the serum levels of UA in patients with POAG are not available.…”
Section: Discussionmentioning
confidence: 94%
“…There is also evidence to suggest that oestrogen is a protective factor against POAG in females and can also influence the levels of UA in the body (Li et al. ,). Overall, the difference between the genders in terms of the association between UA levels and POAG severity may be explained by the differences in oestrogen levels between males and females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations